2006
DOI: 10.1210/en.2005-0648
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effect of Melatonin on Systemic Erythematosus Lupus Developed in Mrl/Mpj-Faslpr Mice: It Ameliorates the Disease Course in Females, whereas It Exacerbates It in Males

Abstract: In this study, the effect of chronic administration of melatonin on MRL/MpJ-Fas lpr mice has been studied. These mice spontaneously develop an autoimmune disease that has many features resembling human systemic lupus erythematosus. In fact, histological studies showed that all female mice and most male mice exhibited glomerular abnormalities, arteritic lesions, and cellular interstitial inflammatory infiltrate ranging from mild to severe patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…It has been shown that melatonin possesses gender-dependent effects on the development of systemic lupus erythematosus. 36 Thus, our gender-specific effects of sildenafil are in the line with the above-mentioned publications.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that melatonin possesses gender-dependent effects on the development of systemic lupus erythematosus. 36 Thus, our gender-specific effects of sildenafil are in the line with the above-mentioned publications.…”
Section: Discussionsupporting
confidence: 89%
“…Several investigations either directly or indirectly supported the relationships between the hormone and the autoimmune process. The administration of melatonin in female lupus MRL/MP-fas mice reduced the levels of autoantibodies and improved the histological changes (22). Since the hormone was added to the drinking water, the exact time of melatonin application could not be specified in the latter study, but it could be of clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin administered in the morning increased the survival of lupus-prone animals, although the effect was not reproduced after evening treatment [255]. Additionally, melatonin reduced vascular lesions and inflammatory infiltration in the kidneys, diminished titers of anti-collagen II and anti-dsDNA autoantibodies, reduced the production of pro-inflammatory cytokines and increased the release of anti-inflammatory cytokines in both female lupus-prone animals [256] and pristane-induced lupus [257]. However, melatonin had no effect or actually worsened the disease in male lupus-prone mice [256].…”
Section: Clinical Relevance Of Melatoninmentioning
confidence: 99%